Предмет: Алгебра,
автор: Хома3
Решите
-(11а+b)-(12a-3b)=
a+(a-10)-(11+a)=
(6x-8)-5x-(4-9)=
2(y-1)-2y+12=
7p-2(3p-1)=
3-17a-11(2a-3)=
Ответы
Автор ответа:
0
-(11а+b)-(12a-3b)= -11а-b-12a+3b=-23a+2b
a+(a-10)-(11+a)=2a-10a-11-a=-9a-11
(6x-8)-5x-(4-9)= x-3
2(y-1)-2y+12=2y-2y+10=10
7p-2(3p-1)=p+2
3-17a-11(2a-3)=-39a-36
a+(a-10)-(11+a)=2a-10a-11-a=-9a-11
(6x-8)-5x-(4-9)= x-3
2(y-1)-2y+12=2y-2y+10=10
7p-2(3p-1)=p+2
3-17a-11(2a-3)=-39a-36
Похожие вопросы
Предмет: Русский язык,
автор: VeRtYcHkA
Предмет: Химия,
автор: lulufed1212
Предмет: Русский язык,
автор: RatnikovaDara
Предмет: Математика,
автор: aisha0525